WELL-BEING PEGAWAI SEBAGAI KUNCI UNTUK MENINGKATKAN REMOTE WORK ENGAGEMENT - Permatasari, Marisa; Amazihono, Memorianus (Jurnal Wahana Bina Pemerintahan, 2023)
The purpose of this study is to analyze the relationship between employee well-being and remote work engagement and to develop a model depicting the relationship between employee well-being and remote work engagement. This study was conducted through a literature review of national and international journal articles published from 1983 to 2023 which were carefully selected, analyzed, and reviewed. The result of the literature review indicates a positive relationship between employee well-being and remote work engagement. Some factors that can improve employee well-being comprise of organizational support, workplace environment and atmosphere, emotional intelligence, and job demands. This study concluded that an employee that able to quickly adapt to workplace environment and condition changes (flexible working arrangement) will increase their well-being and lead to an increase in remote work engagement. The relationship model between employee well-being and remote work engagement developed in this study will serve as the basis for future research to empirically examine the causal relationship between these two variables.